The implementation of multi agent system interface diagnostics PC - Поморова, О. В.; Чайковський, Д. Ю. (Problems of Informatization and Control, 2008)
Description of way users interact with multi-agent systems diagnosing personal computer. The structure of requests and responses informuvan system diagnostics. Shows the production rules that define script processing requests / responses. Examples of dialogue system diagnostics and user